2022
DOI: 10.3389/fpsyt.2021.768279
|View full text |Cite
|
Sign up to set email alerts
|

Temporoparietal Connectivity Within Default Mode Network Associates With Clinical Improvements in Schizophrenia Following Modified Electroconvulsive Therapy

Abstract: Although modified electroconvulsive therapy (ECT) has been reported to be effective for the treatment of schizophrenia (SCZ), its action mechanism is unclear. To elucidate the underlying ECT mechanisms of SCZ, this study used a longitudinal cohort including 21 SCZ patients receiving only antipsychotics (DSZ group) and 21 SCZ patients receiving a regular course of ECT combining with antipsychotics (MSZ group) for 4 weeks. All patients underwent magnetic resonance imaging (MRI) scans at baseline (t1) and follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 51 publications
0
10
0
2
Order By: Relevance
“…Blazer et al ( 2022 ) presented the data of three additional participants compared to Sarpal et al ( 2022a ) in their longitudinal CLZ study. The study on ECT by Huang et al ( 2018 ), Jiang et al ( 2019a , b ), Wang et al ( 2020 ), Hu H. et al ( 2022 ), and Hu Q. et al ( 2022 ) reported on exactly the same patient cohort of 21 TRS individuals receiving a regular course of modified ECT combined with antipsychotics (MSZ), 21 SCZ individuals taking only antipsychotics (DSZ), and 23 HC, although one of the mentioned studies (Hu H. et al, 2022 ) listed (likely by mistake) different age characteristics for DSZ.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Blazer et al ( 2022 ) presented the data of three additional participants compared to Sarpal et al ( 2022a ) in their longitudinal CLZ study. The study on ECT by Huang et al ( 2018 ), Jiang et al ( 2019a , b ), Wang et al ( 2020 ), Hu H. et al ( 2022 ), and Hu Q. et al ( 2022 ) reported on exactly the same patient cohort of 21 TRS individuals receiving a regular course of modified ECT combined with antipsychotics (MSZ), 21 SCZ individuals taking only antipsychotics (DSZ), and 23 HC, although one of the mentioned studies (Hu H. et al, 2022 ) listed (likely by mistake) different age characteristics for DSZ.…”
Section: Resultsmentioning
confidence: 99%
“…During rs-fMRI acquisition, some studies told the participants to keep their eyes open and to look at a fixation cross (White et al, 2016 ; McNabb et al, 2018a , b ; Pillinger et al, 2019 ; Blazer et al, 2022 ; Sarpal et al, 2022a ), while in other studies, they were asked to close their eyes (Alonso-Solís et al, 2015 ; Huang et al, 2018 ; Jiang et al, 2019a , b ; Wang et al, 2020 ; Hu H. et al, 2022 ; Hu Q. et al, 2022 ; Kim et al, 2022 ). Some studies did not report whether the acquisitions were done with open or closed eyes (Ganella et al, 2017 , 2018 ; Gao et al, 2018 ; Yang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electroconvulsive therapy (ECT) is a technique used to treat mental illnesses by applying electrical current through the brain. There is ample clinical evidence that ECT is mainly used in major depressive disorder (MDD), bipolar disorder, schizophrenia ( 15 18 ). However, Current guidelines do not include ECT as an alternative treatment for refractory OCD ( 6 ).…”
Section: Introductionmentioning
confidence: 99%